Exposition humaine aux pesticides : un facteur de risque pour le suicide au Brésil? - Carlos José Sousa Passos (VertigO, 2006)
Over the last decades pesticides have been used to increase agricultural production and eradicate vector born tropical diseases. In parallel, many toxic health effects of pesticide exposure have been identified, and it is currently well known that exposure can impair several biological systems.The aim of this article is to analyse elevated suicide rates in some agricultural regions in Brazil, in light of alternative hypotheses seeking to explain such rates, in particular pesticide exposure. Using an ecosystem approach to human health, we also examine political, economic and cultural factors that can contribute to this problem. Finally, we present an analysis on the public health implications of this problem in Brazil. The review of the literature analyses several studies that support the hypothesis of a possible link between pesticide exposure and elevated suicide rates in Brazil, particularly in the context of family agriculture in the southern regions. This is supported by the international literature suggesting that pesticide exposure can cause neuropsychiatric disorders, which in turn constitute important risk factors to the development of suicidal behaviour.